Internet connectivity disruption in WF (WF) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in WF. Data sourced from IODA.
Network Disruption Incident ID: WF-2026-0003. Severity: critical. Confidence: 65%